1998
DOI: 10.1159/000046449
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Glycoconjugate Analysis

Abstract: Glycoconjugates such as glycoproteins and glycosphingolipids exhibit multiple functions in biological systems. A correlation of functional features with defined structural parameters, however, presupposes detailed information on the glycoconjugates’ carbohydrate moieties including the type of linkage of the oligosaccharide chain(s), monosaccharide composition as well as sequence, linkage positions and anomeric configurations of individual sugar monomers. Chemical and biochemical analyses are often impeded by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 102 publications
0
44
0
Order By: Relevance
“…Some carbohydrate structures are found in all species examined. These are preferentially sugar residues such as mannose and N-acetylglucosamine, which are usually part of the core region of N-linked oligosaccharides, structural depictions for N-glycans being given in this issue by Geyer and Geyer [1998]. The lectin histochemical studies demonstrate that most variations appear to affect the terminal nonreducing region of the ZP sugar chains supporting the idea that even small structural differences may contribute to the establishment of the species-specific nature of gamete interaction.…”
Section: Carbohydrate Composititon Of Zona Glycoproteinsmentioning
confidence: 82%
See 1 more Smart Citation
“…Some carbohydrate structures are found in all species examined. These are preferentially sugar residues such as mannose and N-acetylglucosamine, which are usually part of the core region of N-linked oligosaccharides, structural depictions for N-glycans being given in this issue by Geyer and Geyer [1998]. The lectin histochemical studies demonstrate that most variations appear to affect the terminal nonreducing region of the ZP sugar chains supporting the idea that even small structural differences may contribute to the establishment of the species-specific nature of gamete interaction.…”
Section: Carbohydrate Composititon Of Zona Glycoproteinsmentioning
confidence: 82%
“…Further details on methodological aspects of glycoconjugate analysis and its strategy are outlined in this issue by Geyer and Geyer [1998]. A competition assay revealed that the mixture of neutral chains acts as sperm receptor, while acidic chains have no activity.…”
Section: Carbohydrate Composititon Of Zona Glycoproteinsmentioning
confidence: 99%
“…Structural investigations can be carried out at different levels, including identification of attached carbohydrates by staining procedures, characterization of glycan types by use of glycosidases, lectins, or antibodies, release of sugar chains by chemical or enzymatic treatment, labeling, chromatographic profiling, structural analysis of glycan pools or individual species by MS or NMR spectroscopy, and finally, localization of glycoproteins by immunohistochemical or cytochemical methods (30).…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…If no fucosylation is present and sialylation is incomplete, the sugar structures of N-glycans will expose galactoside-terminated structures, as shown in the chapter by Geyer and Geyer [1998] in this issue, which have become amenable by chemoenzymatic synthesis for assaying their binding affinities [André et al, 1997]. These determinants are docking sites for another class of lectins.…”
Section: Selectins and Integrins: Orchestrated Interplay In Leukocytementioning
confidence: 99%
“…Carbohydrate epitopes for specific binding can be provided both from surface-associated glycoproteins or glycolipids on adjacent cells as well as from carbohydrate chains of adhesive proteins of the basal lamina and the ECM, respectively. Common structural parts of N-glycans of proteins are shown in the chapter of Geyer and Geyer [1998] in this issue. Even the sugar part of neutral glycolipids or gangliosides, structural details being presented by Hakomori [1998] in this issue, can serve as ligand, as convincingly proved for ganglioside GM 1 recently [Kopitz et al, 1998].…”
Section: Introductionmentioning
confidence: 99%